PENGARUH JENIS KEMASAN DAUN NILAM (Pogestemon cablin Benth.) KERING DAN LAMA PENUNDAAN PENYULINGAN TERHADAP RENDEMEN MINYAK NILAM - Nur Hidayat; Desi Wiwis Sahendrati; Nimas Mayang Sabrina Sunyoto (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2012)
The purpose of this research is to determine the effect of dried patchouli leaves (Pogostemon cablin Benth.) packaging type and distillation delay times to the yield of patchouli oil. The raw materials were used the leaves of patchouli (Pogostemon cablin Benth.) obtained from the dried patchouli farmers in Kesamben, Blitar. Experimental design used in this research was randomized block design with two factors consist of the type of packaging and the distillation delay times. Type of packaging used to store the dried patchouli leaves when there was distillation delay times consists of paper and jute sack. The distillation delay times of dried patchouli leaves consist of 5,10, and 15 days. The parameters analyzed including moisture content, total fungi, total bacteria of dried patchouli leaves, and yield of patchouli oil. The results showed that the distillation delay times have more significant influence on moisture content, total fungi and total bacteria than packaging type. Type of packaging, distillation delay times, and interaction between the two factors did not significantly effect the yield of patchouli oil. The best of alternative was the dried patchouli leaves with jute sack packaging and distillation delay times 5 days with a moisture content of 38.46%, total fungi of 7.89 log cfu/g, total bacterial of 9.53 log cfu/g, and a yield of 1.24%. The best treatment result was used as a basis to arrange the dried patchouli leaves in the storage room. The suitable arranged for unit distillation pachouli oil in Blitar was 8 unit in the length and 5 unit in the width of storage room.Keywords : Destilation delay time, Packaging type, Patchouli oil, Pogostemon cablin Benth